2022
DOI: 10.3390/ijerph192013100
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Study of the Mental Health, Resilience, and Post-Traumatic Stress of Senior Nursing Students to Nursing Graduates during the COVID-19 Pandemic

Abstract: This study analyzed changes in the psychological health of students who were in the final year of their nursing degree during the COVID-19 pandemic and later served as nursing professionals in hospitals. Methods: A prospective longitudinal study was conducted over two periods of time (the first in April 2020 and the second 6 months later, in December 2020) with 296 students for a T0 baseline (rate response 68.83%) and 92 students for a T1 post-test sample (response rate 31.08%). The data were electronically co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 35 publications
2
13
1
3
Order By: Relevance
“…In contrast, our results show that women present higher levels of anxiety regarding COVID-19 than men among health professionals, and we found significant differences based on gender. Our results are consistent with those of [ 2 , 5 , 6 , 7 , 11 , 13 , 15 , 20 , 36 , 59 , 69 ], given that female health professionals present greater anxiety regarding COVID-19 compared to male health professionals. This could be due to the caregiver role that women play in their homes, thus resulting in greater anxiety due to the fear of contagion.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In contrast, our results show that women present higher levels of anxiety regarding COVID-19 than men among health professionals, and we found significant differences based on gender. Our results are consistent with those of [ 2 , 5 , 6 , 7 , 11 , 13 , 15 , 20 , 36 , 59 , 69 ], given that female health professionals present greater anxiety regarding COVID-19 compared to male health professionals. This could be due to the caregiver role that women play in their homes, thus resulting in greater anxiety due to the fear of contagion.…”
Section: Discussionsupporting
confidence: 91%
“…This seems to indicate that health professionals tried to protect their psychological health, and therefore their levels of anxiety, in the face of such an unprecedented threat in our recent history. These results support other studies that revealed that positive mental health and social, emotional, and psychological well-being have a positive effect, confer resilience, reduce the negative consequences of unpleasant experiences, promote an adaptive response to uncertain situations, and reduce the risk of suicidal ideation [ 13 , 14 , 24 , 25 , 29 , 30 , 31 , 34 , 36 , 40 , 45 , 49 , 53 , 54 , 82 , 83 , 84 , 85 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations